Suomen valtiojohdon ja Venäjän ulkomaantiedustelun vuorovaikutuksen uudet puitteet Neuvostoliiton hajoamisen jälkeen - Ritvanen, Juha-Matti (Suomen historiallinen seura, 2026)
Relations between the Finnish leadership and foreign intelligence services, especially the Soviet Union's KGB, have aroused wide interest, but research has thus far focused mainly on the Cold War years. After the collapse of the Soviet Union, the KGB's foreign intelligence continued as a separate service known as the SVR (Sluzhba vneshnei razvedki). This article examines the role of the SVR in Finnish-Russian relations. How did Russian intelligence adapt to the post-Soviet situation? The article provides new information, particularly on the interests and methods of Russian foreign intelligence concerning Finland. It is based on documents from the archives of the Ministry for Foreign Affairs of Finland, the personal archives of Presidents Mauno Koivisto and Martti Ahtisaari, and the archives of the Office of the President. Soon after the collapse of the Soviet Union, Finnish president Mauno Koivisto was able to quickly dismantle a decades-old institution under which relations between Finland and the Soviet Union had been managed directly by the president and the head of the KGB in Helsinki since 1956. At the same time, the Finnish leadership and the Finnish Security Police (Suojelupoliisi, Supo) adopted a stricter stance towards Russian intelligence officers operating in Finland. The article shows that at the beginning of President Martti Ahtisaari's term, the strengthening of political influence returned to the agenda of Russian intelligence. This involved efforts to restore the positions of foreign intelligence in the communication between the political leadership of Finland and Russia. The SVR was particularly interested in Finnish politics as a member of the European Union and Finland's relationship with NATO. Information was sought through secret operations and methods, and the recruitment of Finnish individuals as secret agents, much as during the KGB era. The transformation of Russia in the 1990s and Finland's increasingly close integration into the West posed a challenge to Russian intelligence, weakening its operational capacity in Finland. © 2024 Historian Ystavain Liitto. All rights reserved.